2015
DOI: 10.1016/j.ejmech.2015.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the 2-phenyl-4,5,6,7-Tetrahydro-1H-indole as a novel anti-hepatitis C virus targeting scaffold

Abstract: Although all-oral direct-acting antiviral (DAA) therapy for hepatitis C virus (HCV) treatment is now a reality, today's HCV drugs are expensive, and more affordable drugs are still urgently needed. In this work, we report the identification of the 2-phenyl-4,5,6,7-Tetrahydro-1H-indole chemical scaffold that inhibits cellular replication of HCV genotype 1b and 2a subgenomic replicons. The anti-HCV genotype 1b and 2a profiling and effects on cell viability of a selected representative set of derivatives as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…Recently, we have developed a two‐step synthetic methodology that leads to 4,5,6,7‐tetrahydroindoles possessing a wide‐range of substituents both at C 2 or nitrogen atoms (including chiral moieties) ,. This approach bears a general character and is readily scalable to generate sufficient amounts of material on a gram‐scale in good to excellent yields (Scheme , the upper path).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have developed a two‐step synthetic methodology that leads to 4,5,6,7‐tetrahydroindoles possessing a wide‐range of substituents both at C 2 or nitrogen atoms (including chiral moieties) ,. This approach bears a general character and is readily scalable to generate sufficient amounts of material on a gram‐scale in good to excellent yields (Scheme , the upper path).…”
Section: Resultsmentioning
confidence: 99%
“…Last year, we reported a new compound class possessing a 2-phenyl-4,5,6,7-tetrahydro-1H-indole core that inhibits HCV genotype 1b and 2a replication in cells [17,18]. Inspired by this success, we tested an additional set of representative heterobicyclic compounds (1-21 [19][20][21][22], Figure S1 Supporting Information) that was available from the EDASA Scientific public repertory of compound stocks (http://www.edasascientific.com/page/catalogue).…”
Section: Resultsmentioning
confidence: 99%
“…We therefore investigated two representative compounds (6 and 34) for their ability to down-regulate HCV IRESmediated translation [18,25]. Our results indicated that these compounds had no effect on HCV IRES mediated translation even at a higher (25 µM) concentration than is needed to fully inhibit the HCV replicons (data not shown).…”
Section: Scheme 3 Synthesis Of Compounds 30-39mentioning
confidence: 96%
“…Indole derivatives are known to exhibit activities such as antitumour (Andreani et al, 2001); antiviral (Kolocouris et al, 1994) and anti-hepatitis C virus (Andreev et al, 2015). Indoles have attracted much attention because of their wide variety of applications especially in medicinal field.…”
Section: Structure Descriptionmentioning
confidence: 99%